2012
DOI: 10.1038/eye.2012.43
|View full text |Cite
|
Sign up to set email alerts
|

Vitreo-papillary adhesion as a prognostic factor in pseudo- and lamellar macular holes

Abstract: Purpose To determine the incidence of vitreopapillary adhesion (VPA) and to investigate its value as a prognostic factor in the surgical outcome of pseudo-(PMH) and lamellar macular holes (LMH). Methods A total of 76 consecutive patients, diagnosed with PMH (41 eyes) or LMH (35 eyes) were included. Eyes with VPA were alternatively assigned to the surgical or control group. Surgery consisted of a 25G vitrectomy and internal limiting membrane peeling with blue dye staining. There were six visits: baseline, the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
(17 reference statements)
0
11
1
Order By: Relevance
“…It has been previously suggested that the presence of VPA may influence the tangential forces at the vitreoretinal interface, inducing anatomical changes up to the outer retinal layers 27. However our results showed a similar prevalence of outer retinal layer damage in LMH eyes with VPA or with complete PVD.…”
Section: Discussioncontrasting
confidence: 66%
“…It has been previously suggested that the presence of VPA may influence the tangential forces at the vitreoretinal interface, inducing anatomical changes up to the outer retinal layers 27. However our results showed a similar prevalence of outer retinal layer damage in LMH eyes with VPA or with complete PVD.…”
Section: Discussioncontrasting
confidence: 66%
“…In the absence of VPA, inward (centripetal) tangential traction likely throws the underlying retina into folds, resulting in MP. If the vitreous is still attached to the optic disc, the vectors of force could be changed, resulting in outward (centrifugal) tangential traction that induces central retinal dehiscence, MH [ 72 ], and/or ERM [ 73 ].…”
Section: Vitreopapillary Adhesionmentioning
confidence: 99%
“…The patient had no subjective perception that his BCVA had declined. It is sometimes difficult to improve BCVA in patients with pseudo-and lamellar macular holes with vitreous traction [29]. Therefore, caution is required when determining surgical indications in such 13 cases with good BCVA.…”
Section: Discussionmentioning
confidence: 99%